Poboljšanja telekomunikacijskog prometa u ruralnim područjima - Marin, Draško (Promet - Traffic&Transportation, 2012)
This paper deals with certain possibilities of telecommunications service improvement in rural areas with particular reference to social and economic advantages for the inhabitants. Based on the derived relation for respective telephone demand (the relation between the incidence of calls and the distance of telephone locations) it is possible to assess the economic benefits by means of a simulated model of spatial distribution of telephone locations. In relation to the idea of the telecommunications traffic volume and the surplus number of users (the relation of benefits and costs to the user) respective economic benefit reveals and reflects itself in the reduction of the distance travelled by a telephone user in a rural area.